Nocebos in rheumatology: emerging concepts and their implications for clinical practice. Issue 12 (December 2018) - Kravvariti, Evrydiki; Kitas, George; Mitsikostas, Dimos; Sfikakis, Petros
Abstract Nocebo effects are noxious reactions to therapeutic interventions that occur because of negative expectations of the patient. In the past decade, neurobiological data have revealed specific neural pathways induced by nocebos (that is, interventions that cause nocebo effects), as well as the associated mechanisms and predisposing factors of nocebo effects. Epidemiological data suggest that nocebos can have a notable effect on medication adherence, clinical outcomes and health-care policy. Meta-analyses of randomized controlled trials (RCTs) of patients with rheumatic and musculoskeletal diseases (RMDs) indicate that withdrawal of treatment by placebo-arm participants owing to adverse events is common; a proportion of these events could be nocebo effects. Moreover, in large-scale, open-label studies of patients with RMDs who transition from bio-originator to biosimilar therapeutics, biosimilar retention rates were much lower than in previous double-blind switch RCTs. This discrepancy suggests that in addition to the lack of response in some patients because of intrinsic differences between the drugs, nocebos might have an important role in low biosimilar retention, thus increasing the need for awareness and early identification of nocebo effects by rheumatologists and allied health-care professionals. Nocebo effects can occur in patients with rheumatic and/or musculoskeletal diseases, and might result in suboptimal treatment outcomes or non-adherence. The consideration of nocebos is important in rheumatology practice and clinical trial design, including when switching patients to biosimilars. Key points Nocebo effects are noxious changes in a patient's symptoms or physiological condition that occur because of the patient's negative anticipation of treatment, and might result in suboptimal outcomes and non-adherence. Nocebo effects are observed in patients with rheumatic and musculoskeletal diseases, and might hinder the transition of patients to biosimilars. Physicians should be aware of the risk factors for nocebo effects, which can be categorized as features relating to the patient, physician, disease, health-care setting or drug. Physicians should make efforts to measure, prevent and address nocebo effects in clinical practice and interventional trials.